Hd1, Hd3a, and Hd6 Genes : Possible DNA Methylation Roles in Photoperiod Sensitive Gene Regulation of Rice KDML 105 (Oryza sativa L.) - Peerapat Roongsattham; Pradit Pongtongkam; Amara Thongpan; Lily Kaveeta; Poontariga Harinasut; Surin Peyachoknagul (Agriculture and Natural Resources, 2006)
The study was aimed to investigate DNA methylation in rice after treatment with different photoperiods and to determine allelic differences of Hd1, Hd3a, and Hd6 genes, involved in photoperiod sensitivity, in KDML 105, a photoperiod-sensitive cultivar, and in Suphan Buri 1, a photoperiodinsensitive cultivar. Detection of DNA methylation was performed by Southern hybridization. The genomic DNA of KDML 105 was digested by HpaII or MspI restriction enzymes, separated by electrophoresis, Southern blotted and hybridized with probes amplified from the 5’ region of Hd1, Hd3a, and Hd6 genes, respectively. The results showed no difference in band patterns of long-day treatment and short-day treatment of either HpaII or MspI digested groups indicating that the target sequences were not methylated. Primers were designed to amplify the overlapping fragments of Hd1, Hd3a, and Hd6 alleles from rice KDML 105 and Suphan Buri 1 to make a contig sequence covering the whole genes. Nucleotide and deduced amino acid sequences data obtained from this experiment indicated that Hd1, Hd3a, and Hd6 genes of KDML 105 and Suphan Buri 1 encoded normal Hd1, Hd3a, and Hd6 proteins, respectively. Taken together, the data suggested that DNA methylation and single amino acid polymorphisms (SAPs) might not be the mechanisms underlying the expression and function of photoperiod genes. However, the differences of the nucleotide in the 5’ control region might be the cause of the photoperiod sensitivity difference between KDML 105 and Suphan Buri 1.